The Awareness of Clinical Doctors and Medical Students Toward Monkeypox in Jordan: A National Cross-Sectional Study - Aljabali, Ahmed; Alawajneh, Mohammed; Alzamer, Yazan; Altal, Mohammed; Swed, Sarya; Alnawaiseh, Nedal; Elsayed, Mohamed; Sawaf, Bisher; Rakab, Amine (International Journal of Medical Students, 2023)
Background: Following the diagnosis of the first confirmed monkeypox case in Jordan in August 2022, the necessity for assessing the perceived knowledge among healthcare personnel has gained more significance. Given that the knowledge of healthcare professionals plays a great role in protection against newly emerging epidemics, we therefore in this study aim to assess the awareness of medical students and practicing physicians in Jordan toward the monkeypox virus. Method: This cross-sectional study was conducted in Jordan to assess medical students’ attitudes, general practitioners, residents, and specialists regarding the monkeypox virus. Data from the WHO, CDC, and literature were used to design this questionnaire. The questionnaire comprises 53 questions divided into three sections: socio-demographic variables and work-related characteristics, general and specific knowledge about the monkeypox virus. Snowball sampling was employed since it was convenient. The data were analyzed using SPSS version 25.0. A p-value < 0.05 was considered statistical significance. Results: Four hundred twenty-three healthcare professionals participated in this study. Only 7.3% (n = 31) of respondents have ever received information about monkeypox during studies in medicine. Respectively, the mean and median knowledge scores were 12.77 and 13, ranging from 4 to 25. More than half (51.3%, n = 3012) have heard about monkeypox before. About 45.9% (n = 194) of respondents reported that they had heard about monkeypox a few days ago for the first time, while 48.7% (n = 206) heard it a month ago. Most participants had a low level of good knowledge of monkeypox. Only 2.1% of respondents had correctly identified the natural host and the incubation period of monkeypox. More than half (52.1%) correctly answered the sign and symptoms of monkeypox. Almost 49.2% of respondents believed that monkeypox and smallpox have similar signs and symptoms. Respondents aged more than 30 years had higher level of knowledge (COR = 19.45, 95% CI = 6.7683-55.8933, p< 0.001). Respondents who are specialist doctors had higher knowledge of monkeypox (COR = 7.3125, 95% CI = 1.6793-31.8429, p = 0.008) than others. Conclusion: Monkeypox awareness among Jordanian medical students and practitioners is low; hence immediate action should be taken to address this catastrophic problem. Consequently, learning about monkeypox and spreading information about its prevention is crucial. Furthermore, increasing Doctors’ ability to react to human monkeypox cases and report them to a disease surveillance system will depend on their education about the sickness. Keywords: Jordan, Monkeypox, Clinicians, Medical Students, Knowledge.